On the Regional Variability of dB/dt and Its Significance to GIC. Issue 8 (25th August 2020) - Dimmock, A. P.; Rosenqvist, L.; Welling, D. T.; Viljanen, A.; Honkonen, I.; Boynton, R. J.; Yordanova, E.
Abstract: Faraday's law of induction is responsible for setting up a geoelectric field due to the variations in the geomagnetic field caused by ionospheric currents. This drives geomagnetically induced currents (GICs) which flow in large ground‐based technological infrastructure such as high‐voltage power lines. The geoelectric field is often a localized phenomenon exhibiting significant variations over spatial scales of only hundreds of kilometers. This is due to the complex spatiotemporal behavior of electrical currents flowing in the ionosphere and/or large gradients in the ground conductivity due to highly structured local geological properties. Over some regions, and during large storms, both of these effects become significant. In this study, we quantify the regional variability of d B /d t using closely placed IMAGE stations in northern Fennoscandia. The dependency between regional variability, solar wind conditions, and geomagnetic indices are also investigated. Finally, we assess the significance of spatial geomagnetic variations to modeling GICs across a transmission line. Key results from this study are as follows: (1) Regional geomagnetic disturbances are important in modeling GIC during strong storms; (2) d B /d t can vary by several times up to a factor of three compared to the spatial average; (3) d B /d t and its regional variation is coupled to the energy deposited into the magnetosphere; and (4) regional variability can be more accurately captured and predicted from a local index as opposed to a global one. These results demonstrate the need for denser magnetometer networks at high latitudes where transmission lines extending hundreds of kilometers are present. Plain Language Summary: Society is becoming increasingly dependent on technology vulnerable to space weather, meaning that space weather can affect various aspects of our society. The present paper is concerned with geomagnetically induced currents (GICs), which are created by rapid changes in the Earth's geomagnetic field. They flow in long conducting ground infrastructures such as pipelines, power lines, and railways, resulting in negative effects. Predicting GICs is particularly difficult because their underlying driver, the geoelectric field, can change significantly over geographic areas of only several hundred kilometers, which can be considered highly localized. This work aims to understand this regional variability, its dependency on the solar wind, and the effects this has on GICs. The main results from this work are that the rate of change of the geomagnetic field (1) can vary by factors of 3 over 500 km regions, (2) depends on the amount of energy deposited into the Earth's near‐space environment, and (3) can result in GICs which differ by up to 60%. Our results indicate that the local geology is also important to the derivative of the geomagnetic field. These results help to quantify the error in predicting GICs, train new machine‐learning algorithms, and understand the physical mechanisms responsible for this behavior. Key Points: The d B /d t measured by individual stations over a region of 500 km can differ by up to a factor of 3 Regional variability is heavily coupled to solar wind B z and speed Magnetic field spatial variations have an impact on modeling GICs